2022
DOI: 10.1038/s41598-022-11676-w
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic testing by fluorescence in situ hybridization is improved by plasma cell sorting in multiple myeloma

Abstract: Accurate detection of cytogenetic abnormalities has become more important for improving risk-adapted treatment strategies in multiple myeloma (MM). However, precise cytogenetic testing by fluorescence in situ hybridization (FISH) is challenged by the dilution effect of bone marrow specimens and poor growth of plasma cells ex vivo. It has been suggested that FISH should be performed in combination with plasma cell enrichment strategies. We examined cytogenetic abnormalities in newly diagnosed MM and compared th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The 100% intra-patient stability of t (11;14) observed in this study could be attributed to the well-controlled plasma cell input prior to FISH and NGS analysis, obtained after PCE (>80%), or due to improvements in technology and detection methods over the last 6-10 years. Recent studies have demonstrated that PCE is critical to optimize detection of genomic alterations; 14 thus, in the present study, it is possible that t(11;14) was detected in samples in which it would have previously been determined to be undetectable. However, it should be noted that no samples in our study were excluded for having <80% plasma cells after PCE, suggesting that consistent high-level PCE is readily achievable in clinical practice.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The 100% intra-patient stability of t (11;14) observed in this study could be attributed to the well-controlled plasma cell input prior to FISH and NGS analysis, obtained after PCE (>80%), or due to improvements in technology and detection methods over the last 6-10 years. Recent studies have demonstrated that PCE is critical to optimize detection of genomic alterations; 14 thus, in the present study, it is possible that t(11;14) was detected in samples in which it would have previously been determined to be undetectable. However, it should be noted that no samples in our study were excluded for having <80% plasma cells after PCE, suggesting that consistent high-level PCE is readily achievable in clinical practice.…”
Section: Discussionmentioning
confidence: 87%
“…13 A recent study suggested that PCE may be more critical to accurate detection of cytogenetic abnormalities than previously believed, as using PCE improved the detection of abnormalities by direct FISH from 38.0% to 95.5% in diagnostic MM samples 14. This suggests that PCE has strong clinical value for improving FISH-based detection of genomic variability in MM.…”
mentioning
confidence: 99%
“…Other uses of FISH karyotype analysis include genetic diagnosis, prenatal screening, and plant and animal genetic studies [48][49][50][51][52]. But karyotyping is highly dependent on frequency of cytogenetically abnormal cells, in need of enrichment methods such as fluorescenceactivated cell sorter (FACS) to improve the sensitivity [53]. Thus, the combination of FISH with other suitable techniques can compensate for some inherent drawbacks and break the application limitations of FISH.…”
Section: Development Of Fishmentioning
confidence: 99%
“…Plasma cell enrichment methods, such as immunomagnetic or Fluorescence-Activated Cell Sorting (FACS) based on plasma cell antigen expression (e.g., CD138; light chains), are commonly used. 8,9 Other whole cell methods are available to ensure the FISH signal is assessed on plasma cells (e.g., 'target FISH') but are less commonly used. 10 Most FISH analyses are performed on bone marrow samples and rarely on circulating myeloma cells isolated after an enrichment process.…”
Section: Introductionmentioning
confidence: 99%
“…FISH involves the hybridization of fluorescently labeled DNA probes to chromosomal regions of interest and signals overlying counterstained nuclei assessed by fluorescence microscopy. Plasma cell enrichment methods, such as immuno‐magnetic or Fluorescence‐Activated Cell Sorting (FACS) based on plasma cell antigen expression (e.g., CD138; light chains), are commonly used 8,9 . Other whole cell methods are available to ensure the FISH signal is assessed on plasma cells (e.g., ‘target FISH’) but are less commonly used 10 .…”
Section: Introductionmentioning
confidence: 99%